Modern Approaches to Vaccination of Patients with Chronic Liver Diseases and Inflammatory Bowel Diseases against a Novel Coronavirus Infection - A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. To analyze the literature data on the peculiarities of vaccination of patients with chronic liver diseases (CLD) and inflammatory bowel diseases (IBD) against COVID-19 infection.Key findings. It has been shown that many patients with CLD (cirrhosis of the liver, non-alcoholic fatty liver disease) have a higher risk of severe course of a novel coronavirus infection, which necessitates their vaccination. IBD patients are also subject to vaccination, although the immunomodulatory drugs which they take may reduce its effectiveness. In addition, the correct timing of the vaccine administration is of great importance. Vaccination of patients with CLD and IBD is safe, and the frequency of side effects during its implementation does not differ from that in the general population.Conclusion. Analysis of literature data shows that patients with CLD and IBD are subject to vaccination against COVID-19 infection, which is effective and safe.